The Physics of Thin Film Optical Spectra An Introduction - Stenzel, Olaf (Springer Series in Surface Sciences, 2016)
The book bridges the gap between fundamental physics courses (such as optics, electrodynamics, quantum mechanics and solid state physics) and highly specialized literature on the spectroscopy, design, and application of optical thin film coatings. Basic knowledge from the above-mentioned courses is therefore presumed. Starting from fundamental physics, the book enables the reader derive the theory of optical coatings and to apply it to practically important spectroscopic problems. Both classical and semiclassical approaches are included. Examples describe the full range of classical optical coatings in various spectral regions as well as highly specialized new topics such as rugate filters and resonant grating waveguide structures.The second edition has been updated and extended with respect to probing matter in different spectral regions, homogenous and inhomogeneous line broadening mechanisms and the Fresnel formula for the effect of planar interfaces.